Post-operative risk of bisphosphonate-related osteonecrosis complication. Is antimicrobial prophylaxis required in patients classified as low- and medium-risk groups of bisphosphonate-related osteonecrosis complication? - Dziedzic, Arkadiusz; Tanasiewicz, Marta (Journal of Stomatology, 2020)
Dear Editor, With a great interest, we have familiarized ourselves with the latest recently published recommendations of the Polish Dental Association entitled “Rekomendacje Grupy Roboczej Polskiego Towarzystwa Stomatologicznego i Narodowego Programu Ochrony Antybiotyków” (Polish Dental Association and National Programme to Protect Antibiotics Working Group recommendations for administration of antibiotics in dentistry). The first such publication in Poland, of utmost importance for patients, dental practitioners, and scientists, provides the current evidence-based criteria of applying antibiotic therapy as a part of antimicrobial protocol for invasive dental procedures within maxilla-facial region.